Simulation with Fluctuating and Singular Rates (Communications in Computational Physics, 2014)
In this paper we present a method to generate independent samples for ageneral random variable, either continuous or discrete. The algorithm is an extensionof the Acceptance-Rejection method, and it is particularly useful for kinetic simulationin which the rates are fluctuating in time and have singular limits, as occurs for examplein simulation of recombination interactions in a plasma. Although it depends onsome additional requirements, the new method is easy to implement and rejects lesssamples than the Acceptance-Rejection method.